Comparison of Bladder Carcinogens in the Urine of E-cigarette Users Versus Non E-cigarette Using Controls - Fuller, Thomas W.; Acharya, Abhinav P.; Meyyappan, Thiagarajan; Yu, Michelle; Bhaskar, Godugu; Little, Steven R.; Tarin, Tatum V. (Scientific reports, 2018)
Electronic cigarette (EC) use is gaining popularity as a substitute for conventional smoking due to the perception and evidence it represents a safer alternative. In contrast to the common perception amongst users that ECs represent no risk initial studies have revealed a complex composition of e-cigarette liquids. Conventional cigarette smoking is a known risk factor for developing bladder cancer and prior reports raise concern some of those causative compounds may exist in EC liquids or vapor. Urine samples were collected from 13 e-cigarette using subjects and 10 non e-cigarette using controls. Five known bladder carcinogens that are either present in conventional cigarettes, products of combustion, or solvents believed to be used in some e-cigarette formulations were quantified by liquid chromatography – mass spectrometry (LC-MS). Analysis of e-cigarette user urine revealed the presence of two carcinogenic compounds, o-toluidine and 2-naphthylamine, at a mean 2.3 and 1.3 fold higher concentration (p-value of 0.0013 and 0.014 respectively). Many of these subjects (9/13) were long term nonsmokers (>12 months). Further study is needed to clarify the safety profile of e-cigarettes and their contribution to the development of bladder cancer given the greater concentration of carcinogenic aromatic amines in the urine of e-cigarette users.